Research of Rhodiola rosea Rhizomes and Roots Using High Performance Thin Layer Chromatography - N. V. Sklyarevskaya; Yu. S. Alexeeva; A. O. Ponkratova; E. V. Zhokhova (Разработка и регистрация лекарственных средств)
Introduction. The research results obtained through the analysis of different varieties of Rhodiola rosea rhizomes and roots using high-performance thin layer chromatography (HPTLC), grown in the Saint-Petersburg State Chemical-Pharmaceutical University (SPCPU) medicinal plants nursery garden, are represented.Aim. To carry out a comparative analysis of Rhodiola rosea rhizomes and roots samples, grown in the SPCPU medicinal plants nursery using HPTLC.Materials and methods. HPTLC analysis was performed on a CAMAG device (Switzerland), using MERCK HPTLC silica gel 60 F 254, 20 × 10 cm plates. Extracts were obtained from raw materials using an ultrasonic bath "Sapphire-4.0 TTC" (Russia). The Rhodiola rosea rhizomes and roots were harvested in the SPCPU medicinal plants nursery garden (Leningrad Region, Vsevolozhsk district, Priozerskoe Highway, 38 km) in August 2019.Results and discussion. In the course of the research, extracts from Rhodiola rosea rhizomes and roots were obtained using 70 % ethyl alcohol and methyl alcohol as extractants. The extracts were investigated by HPTLC in ethyl acetate – methanol – water – formic acid (77 : 13 : 10 : 2) solvent system. After scanning densitometric analysis at 254 nm, the much better separation of methanol extracts in this solvent system was found than ethanol extracts. The densitograms of individual tracks were compared with each other in order to identify samples of Rhodiola rosea rhizomes and roots with a higher biologically active compounds content. As a result of the comparison of 18 samples tracks of the Rhodiola rosea rhizomes and roots (the extractant was ethyl alcohol 70 %), samples № 6 and 17 have been proposed as promising for further research and cultivation.Conclusion. As a result of the analysis of alcohol extracts from Rhodiola rosea rhizomes and roots by HPTLC, the samples 6 (Tomsk, Russia) and 17 (Valla Di Aposta/Hirvos varieties, country of origin – Italy/Finland) were found to have a higher content of biologically active compounds.